MSA Mimic? Rare Occurrence of Anti-Hu Autonomic Failure and Thymoma in a Patient with Parkinsonism: Case Report and Literature Review - Ricigliano, Vito A. G.; Fossati, Barbara; Saraceno, Lorenzo; Cavalli, Michele; Bazzigaluppi, Elena; Meola, Giovanni (Frontiers in Neuroscience, 2018)
Thymoma is a tumor originating from thymic gland, frequently manifesting with paraneoplastic neurological disorders. Its association with paraneoplastic dysautonomia is relatively uncommon. Here, we describe the challenging case of a 71 year-old female who developed subacute autonomic failure with digestive pseudo-obstruction, dysphagia, urinary tract dysfunction and orthostatic hypotension complicating an underlying extrapyramidal syndrome that had started three months before hospital admission. Autonomic symptoms had 2-month course and acutely worsened just before and during hospitalization. Combination of severe dysautonomia and parkinsonism mimicked rapidly progressing multiple system atrophy. However, diagnostic exams showed thymic tumor with positive anti-Hu antibodies on both serum and cerebrospinal fluid. Complete response of dysautonomia to immunoglobulins followed by thymectomy confirmed the diagnosis of anti-Hu-related paraneoplastic neurological syndrome. With regards to extrapyramidal symptoms, despite previous descriptions of paraneoplastic parkinsonism caused by other antineuronal antibodies, in our case no relation between anti-Hu and parkinsonism could be identified. A literature review of published reports describing anti-Hu positivity in thymic neoplasms highlighted that a definite autonomic disease due to anti-Hu antibodies is extremely rare in patients with thymoma but without myasthenia gravis, with only one case published so far.